Are there hangover-effects on physical performance when melatonin is ingested by athletes before nocturnal sleep? - Atkinson, G.; Buckley, P.; Edwards, B.; Reilly, T.; Waterhouse, J. (International Journal of Sports Medicine, 2001)
Athletes ingest melatonin in an attempt to improve sleep quality or alleviate symptoms of jet lag after transmeridian travel. It is not known whether there are residual effects of this hormone on physical performance in fit subjects. After a sample size estimation involving a meaningful effect on performance of 5%, five milligrams of melatonin or placebo were ingested by twelve physically-active subjects before sleep in a double-blind experiment. The following morning, subjective sleep quality (latency and maintenance) were measured together with intra-aural temperature, grip strength of the left and right hands, and time to complete a 4 km time trial on a cycle ergometer. The subjects also rated perceived exertion during the latter test. The null hypothesis of no effect of melatonin on either subjective sleep quality or physical performance measured the morning after administration could not be rejected on the basis of our observations (P > 0.30). The mean differences between treatments were less than 1% for the strength tests and time trial performance. The confidence intervals for these differences for left and right grip strength and the cycling test were - 2.1 to 2.8 kg, - 3.1 to 2.7 kg and -3.0 to 4.5 s, respectively. In conclusion, it is unlikely that 5 mg of melatonin would have any meaningful effects on physical performance in the morning after fit subjects ingest the hormone. There was also little evidence that it improves sleep quality in this population. Further research is needed concerning the effects of daytime and nighttime admistration of melatonin on performance, in both situations of normal and disturbed sleep.